Pengaruh Penggunaan Media Tangram terhadap Peningkatan Keterampilan Berpikir Kreatif pada Siswa Kelas Lima Sekolah Dasar - Kumfardiah; Hilmiyati, Fitri; Khaeroni (Tarunateach: Journal of Elementary School, 2025)
This study aims to determine the effect of Tangram media on improving students' creative thinking skills in mathematics subjects in grade V. The method used in this study is a quasi-experimental method (Quasi-Experimental Design) more specifically Pretest-Posttest Control Group Design. After the data is collected, the hypothesis testing is carried out using a two-sample independent t-test or Independent Samples t-test. The sample in this study was taken using a purposive sampling technique, with class V A as the experimental class using Tangram media and class V B as the control class not using additional media. The results of this study indicate that Based on the results of SPSS version 20 calculations, the parametric hypothesis test with the Independent Samples t-test obtained a Sig. (2-tailed) value of 0.000 <0.05, then as the basis for decision making in the independent sample t-test it can be concluded that  is rejected and   is accepted, which means that there is a significant influence between the use of tangram media on improving students' creative thinking skills.